Students’ Perception fn the Usage of Hello English Application in Learning English Vocabulary - Anugrah, Nurul; Noni, Nurdin; Sakkir, Geminastiti (Journal of Excellence in English Language Education, 2024)
The purpose of this study was to discover the students’ perception of the usage of the Hello English application in learning English vocabulary at SMP Negeri 2 Sungguminasa. This study applied a quantitative descriptive method. Then, the data was gained through a questionnaire to discover the students’ perceptions after utilizing the Hello English application in learning English vocabulary. Further, the researcher implemented the Likert scale to analyze the data that included five-point scales, namely: strongly concur, concur, indecisive, disagree and strongly disagree. The participants from the study consisted of 30 students from class VIII.9 at SMP Negeri 2 Sungguminasa by applying a cluster-random sampling technique. The study’s finding denoted that the students’ mean score of students’ perceptions after utilizing the Hello English application towards students’ vocabulary mastery was 45.3 which classified as a strongly positive perception. Moreover, the majority of students from this study discerned that the features available in the Hello English application simplify students in their learning activities, and encourage students to learn English, and also, most of them perceive the Hello English application as a pleasurable media to be utilized. Hence, it can be supposed that all of the students discerned positively the usage of the Hello English application as a learning media for learning English vocabulary.